2022
DOI: 10.1177/11779322221142116
|View full text |Cite
|
Sign up to set email alerts
|

Sequence, Secondary Structure, and Phylogenetic Conservation of MicroRNAs in Arabidopsis thaliana

Abstract: MicroRNAs are small non-coding RNA molecules that are produced in a cell endogenously. They are made up of 18 to 26 nucleotides in strength. Due to their evolutionary conserved nature, most of the miRNAs provide a logical basis for the prediction of novel miRNAs and their clusters in plants such as sunflowers related to the Asteraceae family. In addition, they participate in different biological processes of plants, including cell signaling and metabolism, development, growth, and tolerance to (biotic and abio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The secondary structure of the precursors was predicted using the RNAfold web server. 17,27,28,[36][37][38][39][40][41][42] The MFEI values were calculated utilizing the following formula:…”
Section: Data Analysis Of Small Rna Transcriptomementioning
confidence: 99%
“…The secondary structure of the precursors was predicted using the RNAfold web server. 17,27,28,[36][37][38][39][40][41][42] The MFEI values were calculated utilizing the following formula:…”
Section: Data Analysis Of Small Rna Transcriptomementioning
confidence: 99%
“…Although miR165/166 as a cleaver of REV and the role of miRNA effector ARGONAUTE10 (AGO10) were reported in AM initiation 19,37,38 , whether other miRNAs participate in AM development and how they function are unknown. miR394 is a highly conserved miRNA of 20 nucleotides, and rst identi ed in Arabidopsis thaliana 39,40 . Previous studies have reported that miR394 is involved in regulating meristem development, leaf morphogenesis, and stress resistance pathways 41,42,43,44,45,46,47,48,49 .…”
Section: Introductionmentioning
confidence: 99%